Madurese Ethnic Sentiment on Social Media: A Critical Discourse Analysis of The Instagram Account @aslisuroboyo - Arya Purnama, Francisco Dias; Surokim (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines how the Instagram account @aslisuroboyo constructs negative sentiment toward the Madurese ethnic group through crime-related content. Using a qualitative single-case study design, this research applies Norman Fairclough's Critical Discourse Analysis (CDA) across three analytical dimensions: textual, discursive practice, and sociocultural practice. Data were collected from four purposively selected posts published between October 2024 and August 2025. The findings reveal that the account systematically constructs negative sentiment through ethno-geographic identity labeling in visual overlays, transformation of journalistic content into morally charged criminal infotainment, and the operation of othering ideologies rooted in the historical asymmetry between the Javanese-Surabaya and Madurese communities. Notably, the identity labeling mechanism has reached a stage of naturalization, functioning as a structural reflex in content production regardless of the severity of the offense.